Regional differences and convergence tendency of green development competitiveness in China. (1st May 2020) - Zhang, Huan; Geng, Zhirun; Yin, Runsheng; Zhang, Wei
Abstract: Green development competitiveness plays an active role inthe construction of ecological civilization. This researchbuilds a green development competitiveness index system, and measures the competitiveness level of 30 sample provinces in Chinafrom 2003 to 2016 before testing the convergence tendency. It is found that the comprehensive competitiveness of green development in China developed steadily from 2003 to 2016, with the eastern region valuedthe highest, followed by the northeastern, central and western region. The five aspects of evaluation index system for green development competitiveness showed different development tendencies:the competitiveness of green high-quality growth and that of resource conservation and emission reduction sawa steady increase; the competitiveness of urban ecological environment quality and that of green lifestyle remained relatively stable, while the competitiveness of green investment declined slightly. Analysis of regional difference showed that the varying degree of western China was larger than that of eastern, central and northeastern China in order. Besides, the varying degree is becoming larger in eastern and northeastern regions while becoming lower in central and western regions. Convergence analysis showed that from 2003 to 2016, competitiveness level differed from region to region and there were no obvious signs of stochastic convergence at the national level. At the regional level, it can be found that the evaluation values of the eastern region saw stochastic dispersion from the national average. Only four provinces of Henan, Hubei, Guizhou, and Yunnan had possibilities of stochastic convergence to the regional average.